2007
DOI: 10.1017/s0950268807008667
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the control strategies against dengue in Singapore

Abstract: SUMMARYNotified cases of dengue infections in Singapore reached historical highs in 2004 (9459 cases) and 2005 (13 817 cases) and the reason for such an increase is still to be established. We apply a mathematical model for dengue infection that takes into account the seasonal variation in incidence, characteristic of dengue fever, and which mimics the 2004-2005 epidemics in Singapore. We simulated a set of possible control strategies and confirmed the intuitive belief that killing adult mosquitoes is the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
163
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 16 publications
2
163
0
7
Order By: Relevance
“…If this threshold is thereby lowered to a level below the level of control actually achieved, disease transmission may resume, although at a lesser level than previously. It has been suggested that this phenomenon has occurred in Singapore, where rigorous vector control gave good protection against dengue for some years, but a significant number of cases have been recorded in the past several years (Reiter 1993, Ooi et al 2006, Burattini et al 2008.…”
Section: Human Consequences-herd Immunitymentioning
confidence: 99%
“…If this threshold is thereby lowered to a level below the level of control actually achieved, disease transmission may resume, although at a lesser level than previously. It has been suggested that this phenomenon has occurred in Singapore, where rigorous vector control gave good protection against dengue for some years, but a significant number of cases have been recorded in the past several years (Reiter 1993, Ooi et al 2006, Burattini et al 2008.…”
Section: Human Consequences-herd Immunitymentioning
confidence: 99%
“…Another common approach is source reduction of mosquito populations which involves the destruction of mosquito oviposition sites. But it is hard to sustain such interventions successfully over large areas (Lambrechts et al , 2015;Burattini et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was when George Macdonald proposed his expression for what he defined as the "basic reproduction rate" (R 0 ) of malaria. In his words, it is defined as the number of secondary cases produced by a single infected individual (index case) along his/her infectious period in an entirely susceptible population (Macdonald 1952a, Dietz 1993, Massad et al 1994, 2010, Heesterbeek 2002, Lopez et al 2002, Burattini et al 2008. His derivation of R 0 is as follows.…”
mentioning
confidence: 99%